Environmental attitudes and ecological anthropocentrism: a new challenge in environmental higher education - Miklós, Attila (Journal of Education Culture and Society, 2020)
The human-centric nature of environmental thinking is a highly successful adaptation, which has biological, historical, cultural origins. The dichotomy of anthropocentrism and ecocentrism are what ultimately determine ecological attitudes. This nationally representative study presents how students in Hungarian environmental education bachelor programs view the human’s taxonomic position in the world (hierarchies, kinship), throughout evolution (determining possible directions, distancing from other organisms), the role of human power, and our rights of intervention in the environment. It shows what kind of knowledge students arrive with from public education, how they think about handling confl icts, and what impact their acquired knowledge during university years has on their environmental attitudes. It was found that at least two-thirds of students evaluated natural environmental processes, problemsand their consequences with anthropocentric preferences – in contrast to scientifi cally accepted theses.